A Flexing Religius di Media Sosial: Antara Kesalehan dan Eksistensi Diri - Suryadi, Ahmad; Arief, Maryam Jamila (Nubuwwah : Journal of Communication and Islamic Broadcasting, 2026)
The phenomenon of flexingreligious flexing phenomenon on social media shows a change in the way the young Muslim generationexpress piety in the digital space. This research aims toanalyze the forms and motivations behind religious flexing as well as its implications for the meaning of self-authenticity.implications for the meaning of self-authenticity. By using a qualitativeapproach through discourse analysis of posts on Instagram and TikTok as well as interviews with young Muslim creators, it was found that religious expressions are ofteninterviews with young Muslim creators, it was found that religious expressions often functionas a form of personal da'wah and a social existence strategy.social existence strategy. While reinforcing a positive image of Islam, this phenomenon also raises thedilemma between sincerity and self-image. This study emphasizes the need fordigital communication ethics based on the values of sincerity and simplicity in displaying piety online.in displaying piety in cyberspace.